Предмет: Математика,
автор: kristina1810
найдите значение выражения:(х+4)^2-2(х+4)*(х-2)+(х-2)^2; (х-4)^2-2(х+2)*(х-4)+(х+2)^2
Ответы
Автор ответа:
1
(х+4)² - 2(х+4)*(х-2)+(х-2)² = (x+4-(x-2))² = (x+4-x+2)² = (4+2)² = 6² = 36
(х-4)²-2(х+2)*(х-4)+(х+2)² = (x-4-(x+2))² = (x-4-x-2)² = (-4-2)² = (-6)² = 36
P.S. Использована формула квадрата разности:
a²-2ab+b²=(a-b)²
(х-4)²-2(х+2)*(х-4)+(х+2)² = (x-4-(x+2))² = (x-4-x-2)² = (-4-2)² = (-6)² = 36
P.S. Использована формула квадрата разности:
a²-2ab+b²=(a-b)²
Похожие вопросы
Предмет: Математика,
автор: zorokadji5566
Предмет: Геометрия,
автор: fedorovazlata851
Предмет: Алгебра,
автор: hjkeyt
Предмет: Математика,
автор: egorgalikbarov2007
Предмет: География,
автор: Зара7878